Analisis Perbandingan Kinerja Website Statis dan Dinamis dalam Optimalisasi Layanan Informasi Digital - Fadira Az-zahra; Syafira Putri Yuliadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study compares the performance of static and dynamic websites in the context of digital information services. The background of this research is based on the need for organizations and educational institutions to select the right website architecture to provide fast, secure, efficient, and sustainable services. The objective of the study is to analyze the advantages and limitations of each website model from various aspects, including data security, development and maintenance costs, system sustainability, and the ability to integrate with new technologies. The research method uses a descriptive qualitative approach, analyzing relevant current literature, to obtain a comprehensive picture of the technical and non-technical characteristics of both types of websites. The results show that static websites excel in terms of security, initial cost, and system simplicity, but lack flexibility in technology integration. Conversely, dynamic websites excel in flexibility, ease of updating, and readiness to adapt to future technologies, but require higher costs and a robust security strategy. The implication of these findings is the need for a website architecture selection strategy tailored to the organization's needs, resources, and long-term goals.